Desarrollo e implementación de una solución de inteligencia de negocios para la toma de decisiones en la unidad de estadística de la Universidad Nacional de la Amazonía Peruana 2021 - Da Silva de Oliveira Diaz, Renzo Giancarlo (2024)
In the Statistics Unit of the Office of Planning and Budget (OPP), there was a concurrent problem in the data collection and processing process, encountering the inconvenience of not having the information in a timely manner and in real time, and in addition to not being able to have reports that were required to support decision making regarding the preparation of indicators for the Statistical Yearbook. Within the framework of the aforementioned context, the question was raised ¿To what extent will the development and implementation of a Business Intelligence Solution improve Decision Making Support in the Statistics Unit of the National University of the Peruvian Amazon, 2021? Specific objectives were established that allowed evaluating the level of improvement in decision making after developing and implementing the Business Intelligence Solution, it was possible to statistically determine that there were improvements in the process. An Applied study was developed, with a mixed analytical approach, with pre and post test, through which it was determined that there is improvement in the decision-making process. The results showed that all the analyzed indicators show signs of improvement after the development of the solution in general terms, concluding that the users surveyed indicate that there are significant improvements, mainly demonstrating that they have managed to greatly reduce the time required to obtain the necessary reports and statistics to make decisions by the University Statistics Unit.